2012
DOI: 10.1016/j.pharmthera.2011.08.001
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled receptor kinases: More than just kinases and not only for GPCRs

Abstract: G protein-coupled receptor (GPCR) kinases (GRKs) are best known for their role in homologous desensitization of GPCRs. GRKs phosphorylate activated receptors and promote high affinity binding of arrestins, which precludes G protein coupling. GRKs have a multidomain structure, with the kinase domain inserted into a loop of a regulator of G protein signaling homology domain. Unlike many other kinases, GRKs do not need to be phosphorylated in their activation loop to achieve an activated state. Instead, they are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
414
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(428 citation statements)
references
References 441 publications
(672 reference statements)
6
414
0
Order By: Relevance
“…Conversely, we observed that elastase-activated PAR 2 was unable to recruit GRK2, interact with ␤-arrestins, or undergo endocytosis. The lack of GRK2 recruitment by elastase-activated PAR 2 is consistent with the lack of ␤-arrestin recruitment, which is known to rely on GRKmediated phosphorylation of agonist-occupied receptors (57). Our findings support a previous report that elastase-activated PAR 2 is unable to recruit ␤-arrestins (32).…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, we observed that elastase-activated PAR 2 was unable to recruit GRK2, interact with ␤-arrestins, or undergo endocytosis. The lack of GRK2 recruitment by elastase-activated PAR 2 is consistent with the lack of ␤-arrestin recruitment, which is known to rely on GRKmediated phosphorylation of agonist-occupied receptors (57). Our findings support a previous report that elastase-activated PAR 2 is unable to recruit ␤-arrestins (32).…”
Section: Discussionsupporting
confidence: 91%
“…GRKs control the signaling and activation of G protein-coupled receptors (GPCRs) through the phosphorylation of GPCRs [1,2]. Deregulation of GRK-mediated GPCR phosphorylation has been associated with a number of cardiovascular diseases (e.g., hypertension and heart failure) [1][2][3][4], brain diseases (e.g., Alzheimer disease) [1,5], and with certain types of cancers [6,7]. GRK2 (formerly known as b-adrenergic receptor kinase 1) was found to be overexpressed in various brain and cardiovascular diseases, and is therefore considered to be a potential therapeutic target for these diseases [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, consensus substrate motifs for GRK2 were identified from the sequences of GRK2 protein substrates, and 17 candidate peptides were synthesized to identify peptide substrates with high affinity for GRK2. GRK2 appears to require an acidic amino acid at the À2, À3, or À4 positions and its consensus phosphorylation site motifs were identified as (D/ E)X [1][2][3] …”
mentioning
confidence: 99%
“…In mammalian cells, GRK2 is a major feedback inhibitor of GPCRs and has been shown to be implicated among others in psychiatric disorders, immune diseases, and cardiovascular diseases (25)(26)(27). Binding of RKIP to GRK2 inhibits GRK2 kinase activity, which leads to enhanced GPCR signaling.…”
mentioning
confidence: 99%